Cardiovascular disease-linked plasma proteins are mainly associated with lung volume. Issue 2 (27th March 2023) - Rydell, Andreas; Nerpin, Elisabet; Zhou, XingWu; Lind, Lars; Lindberg, Eva; Theorell Haglöw, Jenny; Fall, Tove; Janson, Christer; Lisspers, Karin; Elmståhl, Sölve; Zaigham, Suneela; Melander, Olle; et al.
Background: Epidemiological studies have shown that impaired lung function is common and associated with increased risk of cardiovascular disease. Increased levels of several inflammatory and cardiovascular disease-related plasma proteins have been associated with impaired lung function. The aim was to study the association between plasma proteomics and forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC ratio. Methods: We used a discovery and replication approach in two community-based cohorts, EpiHealth and the Malmö Offspring Study (total n=2874), to cross-sectionally study 242 cardiovascular disease- and metabolism-linked proteins in relation to FEV1, FVC (both % predicted) and FEV1 /FVC ratio. A false discovery rate of 5% was used as the significance threshold in the discovery cohort. Results: Plasma fatty acid-binding protein 4, interleukin-1 receptor antagonist, interleukin-6 and leptin were negatively associated with FEV1 and paraoxonase 3 was positively associated therewith. Fatty acid-binding protein 4, fibroblast growth factor 21, interleukin-1 receptor antagonist, interleukin-6 and leptin were negatively associated with FVC and agouti-related protein, insulin-like growth factor-binding protein 2, paraoxonase 3 and receptor for advanced glycation end products were positively associated therewith. No proteins were associated with FEV1 /FVC ratio. A sensitivity analysis in EpiHealth revealed only minor changes after excluding individuals with known cardiovascular disease, diabetes or obesity. Conclusions: Five proteins were associated with both FEV1 and FVC. Four proteins associated with only FVC and none with FEV1 /FVC ratio, suggesting associations mainly through lung volume, not airway obstruction. However, additional studies are needed to investigate underlying mechanisms for these findings. Several cardiovascular disease-linked proteins were associated with FEV1 and FVC, but not with FEV1 /FVC ratio, suggesting that the relationships are mainly with lung volume, not airflow obstruction https://bit.ly/3j19Io8